Design and fabrication of rear car spoiler for Proton Wira model - Hasbullah, Mat Isa (2007)
Idea to fabricated of spoiler is appear after mass production of accessory on market, this problem will make easily to get some information to fabricated or make it and also to installation. For make the sketch, it specification for a spoiler must be have like an aerodynamic flow on the spoiler. Besides that, beautiful and stylist also will be taken for this fabricate. By using fiberglass as a main material for this project because the fiberglass has their own advantages that it has the higher of strength and it can hardly force until 3 kilogram per time. The fiberglass also becomes the first selection material because it is light compare by using sheet metal. When car is moving speedy on the road, the lift force under the car will increase. It will make instability to the car. With fabricated this spoiler, the driven level of car will be increase and comfortable when this spoiler make stability again. It is because when the car moving speedy, the spoiler will produce the downiorce to make neutral from the lift force.